Optimasi Rute Pendistribusian Obat Pedagang Besar Farmasi di Apotek Kota Kediri menggunakan Algoritma K-Means dan Artificial Bee Colony (ABCKM) - Cindy Cynthia Nurkholis; Imam Cholissodin; Bayu Rahayudi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Pharmaceutical wholesaler is a business that already has a license to distribute pharmaceutical products. In product distribution, there are pharmacies that are close by, no delivery is made, so the courier returns again and gets a larger total distance. Thus, pharmaceutical wholesalers need an optimal route for distributing pharmaceutical products. This problem is a Multi Traveling Salesman Problem (MTSP). The K-Means and Artificial Bee Colony algorithms were chosen to solve the MTSP problem because the K-Means algorithm can be used to share data with the best sources. The solution used in K-Means is the closest neighbor coordinate solution only. So that an artificial bee colony algorithm is needed to help avoid being trapped in the local optima. The artificial bee colony algorithm will be used in finding the optimal route in the problem of optimizing the distribution route of pharmaceutical products at the Kediri City Pharmacy. From the research conducted, it is proven that the ABCKM algorithm is proven to be better than the ABC algorithm and better than using the distribution route carried out by the current courier. From the research, the artificial bee colony algorithm achieves convergence in finding the best solution with a popsize of 70, a limit of 25, and a maximum iteration of 700. From the optimal parameters, the best fitness value is 0.012193.